Governance and public sector reform in Asia : paradigm shifts or business as usual? - Cheung, Anthony; Scott, Ian, 1943- (RoutledgeCurzon, 2003)
This book assesses the current state of governance and public sector reforms in eleven Asian countries and jurisdictions, especially in the wake of the recent regional financial crisis that seriously affected some of them.